In-vivo Pharmacokinetic Study, in-vitro Cytotoxic, Cell Cycle Arresting and Proapoptotic Characteristics of Multiple Emulsions for the Co-delivery of Simvastatin and Alendronate Sodium - Bandgar, Sandip Akaram; Jadhav, Namdeo Ramhari (Indian Journal of Pharmaceutical Education and Research, 2021)
Purpose: Development of nanocarriers that can provide efficient co-delivery of immiscible hydrophilic/ hydrophobic drugs with established technology for industrial production is crucial. Due to this reason, multiple emulsions (MEs) were selected as the desired carriers to achieve the co-delivery ability of many drugs and the improvement of cancer therapeutic effect. MEs could entrap the drug in the inner oil phase and hence avoid the drug leaking and co-deliver the drugs into the tumor sites. Therefore, in the present study, an attempt is made to develop w/o/w multiple emulsion for co-delivery of lipophilic Simvastatin (SVS) and hydrophilic Alendronate Sodium (ADS) with improved oral pharmacokinetics. Methods: The MEs were formulated by the use of Poloxamer-407, TPGS and Soyabean Oil. Tween 80 and Span 80 were used as surfactant and co-surfactant respectively. The MEs was prepared by the process of primary and secondary emulsification and evaluated in terms of visual assessment, turbidity, viscosity, particle size and zeta potential. The optimized batch was evaluated in terms of TEM analysis, X-Ray diffraction, FTIR study, in-vitro release and screened for cytotoxicity study, cell cycle arresting, apoptosis study and quantification of SVS and ADS in Rat Plasma. Results: The MEs treatment inhibited the cell growth with low IC50 value against all cells (A549: 0.030±0.014 µg/mL, MDAMB-231: 0.088±0.013 µg/mL, PC-3: 0.019±0.002 µg/mL).The AUC in case of ADS and SVS was found to be 710.01 ng/mL and 14.413 ng/mL respectively by oral administration and 42.308 ng/mL and 28.902 ng/mL in 12 and 1 hr respectively by IV administration. Conclusion: This strategy has improved simultaneous oral bioavailability of very poorly bio-available both ADS and SVS and thus improved the oral therapeutic efficacy of this combination therapy.
Keywords: Simvastatin; Alendronate Sodium; In-vivo Pharmacokinetic Study; Cytotoxicity Study; Cell cycle arresting; Apoptosis Study